Drucker's lost art of management [ Peter Drucker's timeless vision for building effective organizations - Maciariello, Joseph A.; Linkletter, Karen E. (McGraw-Hill, 2011)
A framework for improving managerial effectiveness, based on the timeless principles of Peter Drucker